Mensuração do tamanho cardíaco em radiografias de gatos com hipertireoidismo experimental - Lahm Cardoso, Mauro José [UNESP]; Costa, Fabiano Sélos [UNESP]; Muniz, Lucy Marie Ribeiro [UNESP]; Zalith, Ana Cristina Aranha [UNESP]; Padovani, Carlos Roberto [UNESP]; Aragon, Flávio Ferrari [UNESP] (My University, 2007)
Feline hyperthyroidism (thyrotoxicosis) is now recognised as the most common endocrine disease of the domestic cat. Feline hyperthyroidism cause multisystemic disorder associated with incresead circulating concentrations of the thyroid hormones, tri-iodothyronine (T3) and thyroxine (T4). Cardiovascular abnormalities in cats with spontaneous hyperthyroid have been described. Objective to determine heart size of progressing experimental thyrotoxicosis of 19 cats, using a vertebral scale system (VHS). The lateral, dorsoventral e ventrodorsal radiographs thoracic were measured using a vertebral scale system. Lateral radiographs thoracic to efficient develop that DV and VD. The VHS method is easy to use, allows objective assesment of heart size in cats hyperthyroid, and may be helpful to identify cardiomegaly and heart size progressing.
Vertebral scale system to measure heart size in radiographs in experimentally hyperthyroidism in the cats
Keywords: Cat; Heart; Hyperthyroidism; Measurements; Radiography; Felidae; Felis catus